Organizational Culture of Sukma Bangsa Learning School (Analytical Study of Learning Organization Primordial Value) - Salabi, Agus Salim; Prasetyo, Muhammad Anggung Manumanoso (Yayasan Sukma, 2022)
This writing is a report study for the development of a learner school management model as well as the acceleration of educational completion with the goal of achieving sustainable education development at the Sukma Nation School of Lhokseumawe. The research focuses on the profile of the school of learners in Sukma Nation, as well as the programâ€™s achievement and problems in its implementation. The research is qualitative in nature and employs survey methods. In terms of data gathered through documentation and interviews with relevant authorities, including focused group observations. The study also presents various manifestations of the Sukma Bangsa School innovations. The results specifically show that institution management refers to the implementation of five primordial grades of learner schools, namely personal mastery, dividing vision, mental models, sitem thinking, and group learning. According to the system, the succession of implementations is seen in changes in individual behavior ranging from knowledge mastery, information distribution, interpretation, and knowledge reminder. Furthermore, the school of learnersâ€™ leadership model has become a critical component of achieving school effectiveness.Penulisan ini merupakan kajian laporan pengembangan model manajemen sekolah peserta didik sekaligus percepatan penyelesaian pendidikan dengan tujuan tercapainya pembangunan pendidikan berkelanjutan di Sekolah Bangsa Sukma Lhokseumawe. Penelitian ini berfokus pada profil sekolah peserta didik di Bangsa Sukma, serta capaian program dan permasalahan dalam pelaksanaannya. Penelitian ini bersifat kualitatif dan menggunakan metode survei. Dalam hal pengumpulan data melalui dokumentasi dan wawancara dengan otoritas terkait, termasuk observasi kelompok terfokus. Kajian ini juga menghadirkan berbagai manifestasi inovasi Sekolah Sukma Bangsa. Hasil penelitian secara khusus menunjukkan bahwa pengelolaan lembaga mengacu pada penerapan lima nilai primordial sekolah peserta didik, yaitu penguasaan pribadi, visi membagi, model mental, pemikiran sistem, dan pembelajaran kelompok. Menurut sistem, suksesi implementasi terlihat pada perubahan perilaku individu mulai dari penguasaan pengetahuan, distribusi informasi, interpretasi, dan pengingat pengetahuan. Lebih jauh lagi, model kepemimpinan siswa sekolah telah menjadi komponen penting untuk mencapai efektivitas sekolah.Â